2022
DOI: 10.3390/biomedicines10051175
|View full text |Cite
|
Sign up to set email alerts
|

CD24 Is a Potential Immunotherapeutic Target for Mantle Cell Lymphoma

Abstract: CD24 and its ligand Siglec-10 were described as an innate immune checkpoint in carcinoma. Here, we investigated this axis in B-cell lymphoma by assessing CD24 expression and evaluating pro-phagocytic effects of CD24 antibody treatment in comparison to hallmark immune checkpoint CD47. In mantle cell lymphoma (MCL) and follicular lymphoma patients, high mRNA expression of CD24 correlated with poor overall survival, whereas CD47 expression did not. Conversely, CD24 expression did not correlate with survival in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…CD24 is highly expressed in multiple tumors and has, thus, been targeted in preclinical trials for lymphoma 65 , 69 , 73 , as well as lung, 14 , 74–76 colorectal, 75 , 77 , 78 bladder, 79 pancreatic, 14 , 74 ovarian, 14 , 74 , 80 liver, 75 , 81–83 breast, 84 and neuroendocrine 14 cancers in addition to osteosarcoma 85 and multiple myeloma 86 ( Table 3 ). Similar to CD20 targeting, the anti-CD24 mAb can bind directly and cluster CD24 to induce apoptosis, recruit NK cells via their Fc receptors to induce ADCC, induce complement-mediated cytotoxicity, as well as the recruitment of phagocytes to the tumor cells.…”
Section: Targeting Cd24 For Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…CD24 is highly expressed in multiple tumors and has, thus, been targeted in preclinical trials for lymphoma 65 , 69 , 73 , as well as lung, 14 , 74–76 colorectal, 75 , 77 , 78 bladder, 79 pancreatic, 14 , 74 ovarian, 14 , 74 , 80 liver, 75 , 81–83 breast, 84 and neuroendocrine 14 cancers in addition to osteosarcoma 85 and multiple myeloma 86 ( Table 3 ). Similar to CD20 targeting, the anti-CD24 mAb can bind directly and cluster CD24 to induce apoptosis, recruit NK cells via their Fc receptors to induce ADCC, induce complement-mediated cytotoxicity, as well as the recruitment of phagocytes to the tumor cells.…”
Section: Targeting Cd24 For Cancer Treatmentmentioning
confidence: 99%
“…62,63 In general, high CD24 expression has been associated with poor prognosis except in the case of multiple myeloma. [64][65][66][67][68][69][70] For chronic lymphocytic leukemia, high CD24 expression was associated with progressive vs stable disease. 71 Even though CD24 has been found to be expressed in most B cell malignancies to date, the protein expression levels do not always differentiate healthy from cancer patients due to high variability in expression.…”
mentioning
confidence: 99%
“…CD24 mAb was found to increase macrophage phagocytosis [ 145 ], which suggests a potential immunotherapeutic target in MCL with the aim of improving innate immunity via disruption of the CD24/SIGLEC-10 axis. Another in vitro study found that CD24 mAb removed more than 90% of MCL cell lines [ 146 ]. Furthermore, CD24 mAb triggered phagocytosis in primary patient-derived MCL cells by autologous macrophages [ 146 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another in vitro study found that CD24 mAb removed more than 90% of MCL cell lines [ 146 ]. Furthermore, CD24 mAb triggered phagocytosis in primary patient-derived MCL cells by autologous macrophages [ 146 ]. Treatment for in vitro MCL cell lines with CD24 mAb was superior to CD47 mAb, which suggests that CD24 mAb may be more effective in treating MCL than CD47 mAb [ 146 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation